1982
DOI: 10.1007/bf02810074
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of human long-term B lymphoblastoid cell lines to chemically defined, serum-free media

Abstract: Attempts were made to adapt human long-term B lymphoblastoid cell lines to prolonged growth in serum-free, chemically defined media. A newly described medium, which is an enriched modification of Dulbecco's modified Eagle's medium containing additional amino acids and vitamins, was used. The serum is totally replaced by albumin, transferrin, and soybean lipid. The cell lines were all adaptable from RPMI 1640 over a period of time during which the 10% fetal bovine serum (FBS) concentration was reduced and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…The overall expression of surface antigens, including the TfR, was not altered by adaptation to serum-free conditions. This is in agreement with the observations of Muzik et al (1982) who found no alterations in surface antigen expression of B-lymphoblastoid cell lines adapted to growth in a serumfree, defined medium. However, the significance of the reduced expression of lactosyl ceramide (CDwl7), complement receptor 1 (CD35) and CD38 observed in the U-937-1SF cells is at present unclear.…”
Section: Response Of U-937-1sf Cells To Selected Cytokines; Ifn-y Tnsupporting
confidence: 93%
“…The overall expression of surface antigens, including the TfR, was not altered by adaptation to serum-free conditions. This is in agreement with the observations of Muzik et al (1982) who found no alterations in surface antigen expression of B-lymphoblastoid cell lines adapted to growth in a serumfree, defined medium. However, the significance of the reduced expression of lactosyl ceramide (CDwl7), complement receptor 1 (CD35) and CD38 observed in the U-937-1SF cells is at present unclear.…”
Section: Response Of U-937-1sf Cells To Selected Cytokines; Ifn-y Tnsupporting
confidence: 93%